Thomas Hobbes: libertad, miedo y resistencia política - Fernández Peychaux, Diego Alejandro (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2014)
This article analyzes the relation the author establishes between freedom and fear, in order to confront it to resistance. First, it studies the definition of liberty held during the debates of XVII century Aristotelianism. Second, it establishes connections between the notion of freedom as a mere act and political resistance. The conclusion reached is that although fear does not constrain freedom nor precludes obligation, this does not imply any limitation to future political resistance.